The Life of Elementary School Subjects on the Q&A Method in Indonesia - Sri Mayleta; Roy Marten; Merni; Janes Glen Ullo; Santri Antie (PT FORMOSA CENDEKIA GLOBAL, 2022)
This research is motivated by the results of observations in the form of interviews with an elementary school in the city of Palangka Raya, Central Kalimantan. The type of research used in this research is qualitative research, the subjects of this research are teachers who in fact dominate the question and answer method system. It is known that most students are very enthusiastic and enjoy the question and answer method learning system, thus helping to support efficiency and effectiveness during the learning activities carried out. In addition, the question-and-answer-based method helps teachers evaluate the level of students' understanding and knowledge of the material explained by the teacher, as well as providing opportunities to attract students' attention and efforts to get direct feedback from students who are involved in the learning process. The question and answer method implied by the teacher in teaching is very closely related to student learning outcomes, because the material delivered by the teacher using the question and answer method affects the cognitive, affective, and psychomotor domains. In this case it can also add religious values ​​to shape the character of students' spiritual knowledge. In this case it can not only shape students' knowledge and spiritual character but also can foster a sense of empathy and sympathy for students towards the people around them.